2008
DOI: 10.1194/jlr.m700446-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipid-bound apoA-I cysteine mutants on lipopolysaccharide-induced endotoxemia in mice

Abstract: HDL has been shown to be able to neutralize the toxicity of lipopolysaccharide (LPS). Our previous study ( J. Lipid Res. 2005. 46: 1303-1311 characterized the properties of secondary structure and in vitro functions of different cysteine mutants of apolipoprotein A-I. Here, we reconstituted recombinant HDLs (named rHDLwt, rHDL52, rHDL74, rHDL107, rHDL129, rHDL173, rHDL195, and rHDL228) by mixing wild type or those mutants with dipalmitoyl phosphatidylcholine and examined their in vivo effects on LPS-induced en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
35
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Apolipoprotein A-I alone can neutralize LPS and this interaction can be altered by changing the structure of apolipoprotein A-I ( 18 ). For example, serine substitution of one cysteine (228) in the C-terminal domain dramatically reduces the ability of HDL to neutralize LPS, whereas substitutions of other cysteines (52 or 74) enhance the ability of HDL to neutralize LPS ( 18 ). The amino acid substitutions that affect LPS neutralization have minimal effects on the lipid composition of HDL.…”
mentioning
confidence: 99%
“…Apolipoprotein A-I alone can neutralize LPS and this interaction can be altered by changing the structure of apolipoprotein A-I ( 18 ). For example, serine substitution of one cysteine (228) in the C-terminal domain dramatically reduces the ability of HDL to neutralize LPS, whereas substitutions of other cysteines (52 or 74) enhance the ability of HDL to neutralize LPS ( 18 ). The amino acid substitutions that affect LPS neutralization have minimal effects on the lipid composition of HDL.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] In particular, the biotransformation of plant lignans, such as secoisolariciresinol diglucoside (SDG), pinoresinol diglucoside (PDG), arctiin, and matairesinol to mammalian lignans, enterodiol (END, 1) and enterolactone (ENL, 2) have extensively been studied. The metabolic processes by intestinal bacteria include deglucosylation, ring cleavage, demethylation, dehydroxylation and oxidation.…”
mentioning
confidence: 99%
“…One of the key defensive functions is the ability of HDL and other lipoproteins to bind endotoxin (lipopolysaccharide, LPS) and other bacterial products and neutralize their toxic effects. In this issue of the Journal of Lipid Research, Wang et al (2) provide insights into the structural requirements for LPS neutralization by apolipoprotein A-I.…”
mentioning
confidence: 99%
“…Thus, Wang et al (2) have shown that, as with cholesterol and phospholipid metabolism, specific regions of apolipoprotein A-I are essential for LPS neutralization. Furthermore, the regions involved in LPS neutralization are different than those involved in cholesterol and phospholipid metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation